Clinical, pathological, and immunohistochemical findings in bald eagles (Haliaeetus leucocephalus) and golden eagles (Aquila chrysaetos) naturally infected with West Nile virus - Wuenschmann, Arno; Timurkaan, Necati; Armien, Anibal G.; Padilla, Irene Bueno; Glaser, Amy; Redig, Patrick T. (Sage Publications Inc, 2014)
Fifteen bald eagles (Haliaeetus leucocephalus) and 3 golden eagles (Aquila chrysaetos) were diagnosed with West Nile disease based on 1) presence of lesions in brain, eyes, and heart, 2) viral antigen detection in brain, eyes, heart, kidney, and/or liver by immunohistochemical staining, 3) detection of viral RNA in tissue samples and/or cerebrospinal fluid (CSF) by polymerase chain reaction, and/or 4) detection of West Nile virus (WNV)-specific antibodies in CSF by serum neutralization assay. West Nile virus-associated gross lesions included cerebral pan-necrosis with hydrocephalus ex vacuo (7/15 bald eagles), fibrin exudation into the fundus in 1 golden eagle, retinal scarring in 1 bald eagle, and myocardial pallor and rounded heart apex in 4 bald eagles. Histologic lesions included lymphoplasmacytic encephalitis, most prominently in the cerebrum (17 eagles), lymphoplasmacytic pectenitis and choroiditis (15 and 8 eagles, respectively), and myocarditis (12 eagles). West Nile virus antigen was detected in the majority of the eagles in neurons of the brain (cerebrum and cerebellum), and less commonly present in neurons of the retina, tubular epithelial cells of the kidney, and cardiomyocytes. West Nile disease was diagnosed in 2 bald eagles based on the presence of cerebral pan-necrosis and WNV-specific antibodies in the CSF despite lacking viral antigen and RNA. In conclusion, WNV infection causes a fatal disease in bald and golden eagles. A variety of gross and histologic lesions are highly suggestive of WN disease in most eagles. A combination of detection of viral antigen and/or RNA or virus-specific antibodies proved useful in confirming the diagnosis.
Keywords: Aquila chrysaetos; bald eagles; golden eagles; Haliaeetus leucocephalus; West Nile virus